2019
DOI: 10.1177/0306307019872304
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance factors as predictors of earnings management

Abstract: Unlike developed markets, emerging markets like India have greater imperfections, have information asymmetry, and are particularly different in terms of accounting transparency, corruption, and corporate governance (CG). Also, concentrated ownership structure of Indian firms is more conducive for opportunistic earnings management (EM). There has been high incidence of financial frauds and EM in India particularly through related party transactions. The CG regulations were revised and enhanced in the year 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 162 publications
(188 reference statements)
3
21
2
Order By: Relevance
“…Kent et al (2016) measured EQ by capturing earnings manipulation and the uncertainty of accruals, and this measurement is supported by Dechow and Dichev (2002), Francis et al (2005), Jones et al (2008), and Dechow et al (2010). Beyer et al (2019) measured EQ by predicting about the time-series properties of financial information and reporting bias (Wasan & Mulchandani, 2020). Mehrani et al (2017) discussed that we can measure the EQ by earnings response coefficient, discretionary accruals, predictive value of earnings, conservatism, and real earnings management.…”
Section: Measurements Of the Study Variablesmentioning
confidence: 90%
See 1 more Smart Citation
“…Kent et al (2016) measured EQ by capturing earnings manipulation and the uncertainty of accruals, and this measurement is supported by Dechow and Dichev (2002), Francis et al (2005), Jones et al (2008), and Dechow et al (2010). Beyer et al (2019) measured EQ by predicting about the time-series properties of financial information and reporting bias (Wasan & Mulchandani, 2020). Mehrani et al (2017) discussed that we can measure the EQ by earnings response coefficient, discretionary accruals, predictive value of earnings, conservatism, and real earnings management.…”
Section: Measurements Of the Study Variablesmentioning
confidence: 90%
“…Regarding the measurement of earnings quality as an independent variable, the prior studies disagree about the measurement of earnings quality (Srinidhi et al, 2011;Beyer et al, 2019;Wasan & Mulchandani, 2020). Srinidhi et al (2011) measured EQ by current discretionary accruals which are related to financial statements.…”
Section: Measurements Of the Study Variablesmentioning
confidence: 99%
“…Hamdan (2020b) reveals that audit committee persistence/meeting has no impact on earnings quality. On the other hand, Wasan and Mulchandani (2019) showed that the frequency of audit committee meetings affects earnings quality. The more active they participate in meetings, the more effective the complaint committee is and the better the quality of earnings reported by management.…”
Section: Frequency Of Audit Committee Meetings and Earnings Qualitymentioning
confidence: 99%
“…The agency approach shows that the existence of an independent commissioner in the board of commissioner structure is a key feature of an effective corporate governance framework [25] and can reduce agency costs arising from the separation of ownership and control. Independent commissioners can carry out monitoring effectively [26], [27], thereby increasing earnings quality by reducing opportunities for earnings management and fraud actions by people in the company [28]. [29] found that the existence of independent commissioners in companies in the UK was able to suppress earnings management levels with real activities.…”
Section: Literature Reviewmentioning
confidence: 99%